Isolation and charaterization of Vibrio cholerae O1 from stools of diarrheal patients and studies of the methods to determine the immunological responses - Khan, Md. Saifur Rahman (BRAC University, 2010)
This thesis is submitted in a partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2008